2007
DOI: 10.1002/bdrc.20111
|View full text |Cite
|
Sign up to set email alerts
|

New insights into elastic fiber assembly

Abstract: Elastic fibers provide recoil to tissues that undergo repeated stretch, such as the large arteries and lung. These large extracellular matrix (ECM) structures contain numerous components, and our understanding of elastic fiber assembly is changing as we learn more about the various molecules associated with the assembly process. The main components of elastic fibers are elastin and microfibrils. Elastin makes up the bulk of the mature fiber and is encoded by a single gene. Microfibrils consist mainly of fibril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
354
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 355 publications
(378 citation statements)
references
References 108 publications
13
354
1
Order By: Relevance
“…36 No disease has been associated with BGN mutation in humans but Bgn-deficient mice have a skeletal phenotype. 37 Lysyl oxidase (Lox gene) may be important in overall assembly of elastic microfibrils (reviewed in Wagenseil and Mecham 38 ) and may be involved in preparing tumour cells for metastasis. 39 The human homologue of another of the cluster genes, SERPINH1, was recently implicated in a recessive form of osteogenesis imperfecta, a bone disease.…”
Section: Discussionmentioning
confidence: 99%
“…36 No disease has been associated with BGN mutation in humans but Bgn-deficient mice have a skeletal phenotype. 37 Lysyl oxidase (Lox gene) may be important in overall assembly of elastic microfibrils (reviewed in Wagenseil and Mecham 38 ) and may be involved in preparing tumour cells for metastasis. 39 The human homologue of another of the cluster genes, SERPINH1, was recently implicated in a recessive form of osteogenesis imperfecta, a bone disease.…”
Section: Discussionmentioning
confidence: 99%
“…Mature elastin chains are cross-linked by desmosine linkages formed among most lysine residues (18,19). Elastin is "rubber-like," amorphous by x-ray fiber diffraction, and does not crystallize (20).…”
mentioning
confidence: 99%
“…Mature elastin fibrils are insoluble, extensible, and intimately mingled with collagen, fibulin, other glycoproteins, and polysaccharides such as chondroitin sulfate (17)(18). Mature elastin chains are cross-linked by desmosine linkages formed among most lysine residues (18,19).…”
mentioning
confidence: 99%
“…[23] In contrast to the complex assembly of collagen type I, which relies on multiple proteolytic processing steps of the associating heterotrimer units, [25] tropoelastin is more amenable to study because its unprocessed monomers assemble on the path to elastin. [26] Multiple laboratories [27,28,29] have elegantly explored how microfibrils contribute to the distribution of elastin in vivo and that low-abundance molecules such as fibulins are needed for elastic fibre organization in vivo. [30] [31] Over the past few years, we and others have found that, in vitro, these molecules are not needed for the spatial and temporal elastin assembly of tropoelastin.…”
Section: Tropoelastin Assemblymentioning
confidence: 99%
“…[42] The benefit of low thrombogenicity appears to be concentrated in a region from the N-terminus to domain 10 whereas endothelialization appears to be conferred by two autonomously functional regions: the central [43] and the C-terminus of tropoelastin. [44] Given the transient nature of tropoelastin in vivo before crosslinking into elastin, [27,45] these effects are presumably a feature of elastin or subregions within elastin. Tropoelastin elicits potent tropoelastin-promoted neoangiogenesis in mice and sheep and enhanced wound closure through accelerated epithelialization [46] but it is not yet known which part(s) of tropoelastin contribute(s) this effect, although endothelial cells recognize elastin by upregulating nitric oxide production by endothelial nitric oxide synthase through a phosphatidylinositol-4,5-bisphosphate 3-kinase pathway.…”
Section: Concluding Commentsmentioning
confidence: 99%